Optical and structural characterization of oleic acid-stabilized CdTe nanocrystals for solution thin film processing - Gutiérrez-Lazos, Claudio Davet; Ortega-López, Mauricio; Pérez-Guzmán, Manuel A.; Espinoza-Rivas, A. Mauricio; Solís-Pomar, Francisco; Ortega-Amaya, Rebeca; Silva-Vidaurri, L. Gerardo; Castro-Peña, Virginia C.; Pérez-Tijerina, Eduardo (Beilstein Journal of Nanotechnology, 2014)
This work presents results of the optical and structural characterization of oleic acid-stabilized cadmium telluride nanocrystals (CdTe-NC) synthesized by an organometallic route. After being cleaned, the CdTe-NC were dispersed in toluene to obtain an ink-like dispersion, which was drop-cast on glass substrate to deposit a thin film. The CdTe-NC colloidal dispersion as well as the CdTe drop-cast thin films were characterized with regard to the optical and structural properties. TEM analysis indicates that the CdTe-NC have a nearly spherical shape (3.5 nm as mean size). Electron diffraction and XRD diffraction analyses indicated the bulk-CdTe face-centered cubic structure for CdTe-NC. An additional diffraction line corresponding to the octahedral Cd3P2 was also detected as a secondary phase, which probably originates by reacting free cadmium ions with trioctylphosphine (the tellurium reducing agent). The Raman spectrum exhibits two broad bands centered at 141.6 and 162.3 cm−1, which could be associated to the TO and LO modes of cubic CdTe nanocrystals, respectively. Additional peaks located in the 222 to 324 cm−1 range, agree fairly well with the wavenumbers reported for TO modes of octahedral Cd3P2.
Keywords: cadmium telluride; Raman spectroscopy; semiconductor nanocrystals; transmission electron microscopy; X-ray diffraction